Cholera treatment with beetroot based ORS in malnourished children - Atif Amin, Baig; Chandrika, Murugaiah; Jasvinder, Kaur (2019)
Cholera is an infection caused by the bacterium Vibrio cholerae that causes severe watery diarrhea, which can lead to dehydration. Symptoms may range from none, to mild, to severe with vomiting that may result in sunken eyes, cold skin, decreased skin elasticity, and wrinkling of the hands and feet. It is caused by eating food or drinking water contaminated with a bacterium called Vibrio cholerae with symptoms start two hours to five days after exposure. Malnutrition in cholera is a condition that results from insufficient eating a diet in which one or more nutrients are either not enough that the diet causes health problems. Deficit may involve calories, protein, carbohydrates, vitamins or minerals. Normally malnourished children experience undernutrition or undernourishment where the childen is not getting enough calories, protein, or micronutrients. Malnutrition increases the risk weakens immune system. In cholera, protein and energy malnutrition and deficiencies of specific micronutrients (including iron, zinc, and vitamins) increase susceptibility to infection. Diarrhea and other infections can cause malnutrition through decreased nutrient absorption, increased metabolic requirements, direct nutrient loss, and decreased intake of food.